AB1050 Subclinical Ultrasonographic Enthesopathy and Synovitis in Patients with Inflammatory Bowel Disease Without Clinical Signs or Symptoms of Spondyloarthritis. (9th June 2015) - Vicente, E.; Pérez, S.; Merino, L.; Llorente, I.; Chaparro, M.; Rodríguez-Salvanés, F.; Vega, L.; Castañeda, S.; Gisbert, J.P.
Abstract : Background: Musculoskeletal manifestations are present in 10-62% of Inflammatory Bowel Disease (IBD) patients. As ultrasonography is more sensitive than physical examination to detect enthesopathy and synovitis, we believe it may be useful to identify subclinical involvement. Objectives: To evaluate the presence of subclinical enthesitis and synovitis with power Doppler ultrasonography (PDUS) in IBD patients and to investigate its correlation with IBD variables. Methods: Cross-sectional study that recruited prospectively IBD patients, without clinically overt musculoskeletal disease, attended by Gastroenterology. Gastroenterological, rheumatological and PDUS evaluation, blind to each other, were performed. Clinical assessment included demographics, comorbidities, IBD characteristics and musculoskeletal clinical examination. PDUS evaluation consisted of the detection of grey scale (GS) and power Doppler (PD) signs of enthesopathy and synovitis scored by MASEI index and a 44 joint-count, respectively, using a LOGIQ7 General Electric machine. Statistical analysis: The associations between PDUS and clinical variables were evaluated by the Student's t test, Mann-Whitney test, χ2 or Pearson and Spearman correlations as appropriate. The intra-reader agreement for US was estimated in all the images obtained. Statistical significance was set at p<0.05 (Stata 10). Results: 35 (51% male) IBD patients, 17 Crohn's disease (CD) and 18 ulcerative colitis (UC), have been included so far. Clinical variables: Age 42±12 years, evolution time 9.5 years (range: 0.1-33), CDAI 20.5±17.5, Mayo index 0.4±0.9, DMARD therapy in 98.6% for 5.5±5.3 years, ESR 12.4±8 mm/h and CRP 0.13±0.19 mg/dL. A positive MASEI was present in 98.6%, with a mean score of 33.1±8.8. GS enthesal abnormalities were found in at least 1 enthesis in 100% of patients: enthesophytes or calcifications (100%), altered echoestructure (100%), increased thickness (100%), erosion (17%) and bursitis (34.3%). The most severely affected enthesis were Achilles tendon and plantar fascia. GS joint effusion and synovial hypertrophy (SH) in at least 1 joint were present in 85.7% and 94.3%, respectively, with poliarticular (≥5 joints) involvement in 40% and 60%, respectively. Entheseal and joint PD signal was positive in 42.8% and 40% of patients, respectively. Joint effusion and synovial hypertrophy were more frequent in MTF, MCF, carpal and knee joints and PD signal in carpal and knee joints. SH scores were significantly higher in UC than in CD (p=0.003). SH and PD scores were associated with age (p=0.011 and p=0.002). We found no other association between PDUS variables and clinical or analytical IBD variables, probably due to the sample size. The intra-reader agreement was high (0.8 intra-class correlation variability). Conclusions: Subclinical joint and entheseal PDUS abnormalities are common in IBD patients, regardless of clinical subtype, evolution time and intestinal activity. SH seems more severe in UC than CD. Prospective longitudinal studies are needed to define its predictive value of clinically overt musculoskeletal disease and its association with structural deterioration. Disclosure of Interest: None declared